2017
DOI: 10.1111/joes.12219
|View full text |Cite
|
Sign up to set email alerts
|

Taking Stock: A Rigorous Modelling of Animal Spirits in Macroeconomics

Abstract: This paper is a survey of the burgeoning literature that seeks to take the enigmatic concept of the animal spirits more seriously by building heterodox macro‐dynamic models that can capture some of its crucial aspects in a rigorous way. Two approaches are considered: the discrete choice and the transition probability approach, where individual agents face a binary decision and choose one of them with a certain probability. These assessments are adjusted upward or downward in response to what the agents observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Other choices range from regressive techniques to rational expectations. The interested reader is referred to the excellent work of Franke and Westerhoff (2017) and references therein for a survey of modelling of animal spirits.…”
Section: The Role Of Expectations On Credit Demandmentioning
confidence: 99%
“…Other choices range from regressive techniques to rational expectations. The interested reader is referred to the excellent work of Franke and Westerhoff (2017) and references therein for a survey of modelling of animal spirits.…”
Section: The Role Of Expectations On Credit Demandmentioning
confidence: 99%
“…Such transition rates, which yield the evolution equation different from equation ( 11), may be unrealistic as they are asymptotically unbounded. In addition, the transition rates given by equations (10) patch up the differences, discussed in Franke and Westerhoff (2017), between the transition probability (Weidlich andHaag 1983, Lux 1995) and discrete choice Hommes 1997, 1998) approaches to modeling opinion dynamics.…”
Section: Derivation Of Model Equationsmentioning
confidence: 99%
“…A comprehensive review of expectation formations in macroeconomics can be found in Assenza et al. ( 2013 ) and Franke and Westerhoff ( 2018 ).…”
Section: Introductionmentioning
confidence: 99%